Molecular and clinical evaluation of the acute human parvovirus B19 infection: comparison of two cases in children with sickle cell disease and discussion of the literature - Svetoslav Nanev Slavov; Simone Kashima; Ana Cristina Silva-Pinto; Alberto Anastacio Amarilla; Victor Hugo Aquino; Dimas Tadeu Covas (Brazilian Journal of Infectious Diseases, 2013)
Human parvovirus B19 is a well-known cause of severe conditions in patients with sickle cell disease, but the molecular mechanisms of the infection are insufficiently understood. The different clinical outcome of the acute parvovirus B19 infection in two pediatric patients with sickle cell disease has been examined. One of them developed life-threatening condition requiring emergency transfusions, while the other had asymptomatic infection, diagnosed occasionally. Both cases had high viral load and identical subgenotype, indicating that the viral molecular characteristics play a minimal role in the infection outcome.